Investigating the causes of language anxiety among future primary school teachers in foreign language classes - Haroud, Samia; Ouchaouka, Lynda; Saqri, Nadia (Frontiers in Education, 2025)
The acquisition of a second language frequently induces anxiety among students, particularly in speaking situations. This anxiety often stems from linguistic insecurity, fear of mispronunciation, and perceived judgment from both instructors and peers. Proficiency in public speaking is a critical goal in teacher training programs and is progressively developed throughout the education of prospective teachers. This study examines the level of language anxiety among future primary school teachers at the Higher Normal School of Casablanca, identifies the factors contributing to this anxiety, and proposes strategies to mitigate it. The findings reveal that anxiety arises from diverse factors, including fear of negative evaluation, lack of confidence, and insufficient opportunities for oral practice. These results underline the importance of teacher training programs in addressing emotional barriers through tailored strategies such as collaborative learning activities, gradual exposure to speaking tasks, and explicit training on coping mechanisms. Implementing these methods could help prospective teachers not only overcome their own anxiety but also equip them to support their students effectively in language learning environments. By linking the findings to practical implications, this study highlights the necessity of integrating emotional support mechanisms into teacher training programs. Such initiatives aim to foster both linguistic competence and emotional well-being, ensuring future educators are better prepared to create inclusive and supportive classroom environments.